▼Xiapex for Dupuytren's contracture. Issue 12 (14th December 2011) - Unknown
Abstract : Dupuytren's contracture is a benign, progressive disabling condition of the hands.1 2 Traditionally, surgery (e.g. fasciotomy, fasciectomy, joint fusion and amputation) has been the only effective treatment but it is not an option for every patient.3 4 A potential alternative intervention is a formulation of collagenase Clostridium histolyticum (▼Xiapex - Pfizer Limited), which has been licensed for injection directly into the affected joint as treatment for adults with Dupuytren's contracture.5 Here we review the evidence for collagenase C. histolyticum and discuss its place in the management of this condition.